Wavelet-based analysis and detection of fault-induced transients in HVDC systems - Silva, Daniel Marques da (2018)
A fast and accurate detection of the transients is essential to ensure a reliable protection system capable to act with high-speed. In this research, a theoretical foundation regarding the high-voltage direct current (HVDC) transmission systems, traveling waves, and the wavelet transform is provided. Then, a qualitative analysis of the traveling waves induced by faults on direct current (DC) transmission lines of HVDC systems is presented for detecting the wavefront arrival times using the boundary wavelet coefficients from real-time boundary stationary wavelet transform (RT-BSWT). This qualitative analysis takes into account the steady-state, and the detection of the inception times of both first and second wavefronts at the converter stations. The behavior of the boundary wavelet coefficients in DC transmission lines is examined considering the effects of the main parameters that influence the detection of the traveling waves, such as mother wavelets, sampling frequency, DC transmission line terminations, as well as fault resistance and distance. An algorithm designed to run in real-time and able to minimize the factors that hamper the performance of traveling wave-based protection (TWP) methods is presented to detect the traveling wave arrival times. Quantitative results are achieved based on the accuracy of one- and two-terminal fault location estimation methods, and indicate the proper operation of the presented algorithm.